Cholecystocolic fistula diagnosis with hepatobiliary scintigraphy: A case report. Issue 1 (1st November 2018) - Mallick, Bipadabhanjan; Bhattacharya, Anish; Gupta, Pankaj; Rathod, Srinath; Dahiya, Divya; Dutta, Usha
Abstract : We report a 62‐year‐old woman who presented with chronic watery diarrhea and weight loss. During evaluation, she was found to have pneumobilia in the absence of gallstones, raising the suspicion of bilioenteric communication. Computed tomography demonstrated adherence of the gallbladder to the adjacent transverse colon. Hepatobiliary scintigraphy demonstrated the presence of a cholecystocolic fistula. A planned uneventful open cholecystectomy with resection of fistulous tract and closure of colonic opening was performed, resulting in the complete resolution of clinical symptoms. Abstract : A 62‐year‐old lady with bilio‐enteric communication presented as case of chronic diarrhea. Computed tomography revealed adherence of gallbladder to adjacent transverse colon. Hepatobiliary scintigraphy demonstrated the presence of a cholecystocolic fistula.